2020
DOI: 10.1177/1747493020954946
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality in survivors of spontaneous intracerebral hemorrhage

Abstract: Background Factors associated with long-term mortality after spontaneous intracerebral hemorrhage (ICH) have been poorly investigated. Aim Our objective was to identify variables associated with long-term mortality in a prospective cohort of 30-day ICH survivors. Methods We prospectively included consecutive 30-day spontaneous ICH survivors. We evaluated baseline and follow-up clinical characteristics and magnetic resonance imaging (MRI) markers of chronic brain injury as variables associated with long-term mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…People who undergo ICH treatment have a high incidence of recurrent haemorrhagic stroke, which accounts for a significant elevation in incidence compared with those who first suffer from ICH (Chu et al, 2020). Previous studies have confirmed that the high-risk factors related to ICH are lobar haematoma location, race/ethnicity and apolipoprotein (APOE) gene mutations (chiefly cortical superficial siderosis and cerebral microbleeds) (Lorente et al, 2020;Pasi et al, 2020;Sykora et al, 2020). Since ICH seriously threatens the health of elderly people, it is urgent to develop a new method for the treatment of ICH.…”
Section: Introductionmentioning
confidence: 99%
“…People who undergo ICH treatment have a high incidence of recurrent haemorrhagic stroke, which accounts for a significant elevation in incidence compared with those who first suffer from ICH (Chu et al, 2020). Previous studies have confirmed that the high-risk factors related to ICH are lobar haematoma location, race/ethnicity and apolipoprotein (APOE) gene mutations (chiefly cortical superficial siderosis and cerebral microbleeds) (Lorente et al, 2020;Pasi et al, 2020;Sykora et al, 2020). Since ICH seriously threatens the health of elderly people, it is urgent to develop a new method for the treatment of ICH.…”
Section: Introductionmentioning
confidence: 99%
“…Both pre-stroke dependency and cerebral global atrophy were found to be predictors of long-term mortality in the PITCH cohort when including 30-day survivors of all ages, as well as higher age, male sex, higher NIHSS at baseline and any recurrent stroke or dementia during follow-up. 18 In these young 30-day ICH survivors, cerebral atrophy was the only radiological predictor of long-term mortality. An explanation could be that cerebral atrophy can be considered as an expression of severe brain damage secondary to both cerebral small vessel disease and neurodegeneration (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Excessive alcohol consumption was not found to be predictive of long-term mortality in the PITCH cohort of all ages and therefore may be specific to this young subgroup of this cohort. 18 Previously, excessive alcohol consumption has been shown to be associated with a higher mortality risk in ICH patients of all ages. 11,22 The Finnish hospital-based study found male sex and diabetes at baseline to be predictors of long-term mortality, however they did not take alcohol use, mRS pre-ICH or MRI-markers into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations